A systematic review of engineering properties of magnesium potassium phosphate cement as a repair material - Dabarera, Arosha; Fernández, Raúl; Provis, John L. (Frontiers in Materials, 2024)
Magnesium phosphate cement (MPC) is known as a high-performing rapid repair material for concretes in practice, and has also become a fast-moving research area for other applications, although its application has not yet reached its full potential. MPC has been utilized as a repair material in certain applications, although it is still less commonly used/recommended than the most popular and standardized repair materials. Therefore, it is important to systematically investigate the suitability of this material in the construction sector as a repair material. This review provides an in-depth summary of the engineering properties of magnesium potassium phosphate cements (MKPCs), as a particular example of MPCs that do not suffer from the undesirable release of ammonia which is observed in some other MPC formulations. Key properties relevant to the use of MKPCs as repair materials, from the fresh state to the hardened state are systematically examined. On this basis, the suitability of MKPC as a potential repair material is explored, highlighting the state-of-the-art practices, challenges and drawbacks in engineering applications, and future perspectives.